1994
DOI: 10.3801/iafss.fss.4-1017
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Fuel Spill Fires Under The Wing Of An Aircraft

Abstract: As part of a probablistic risk assessment program, estimates of the thermal exposure in aircraft crash fires were needed. Tests were conducted to simulate he1 spill fires that might occur under the wing of a C-141 transport aircraft. Measurements were made of the fire temperatures and the heat fluxes to the underside of the wing and the underwing hselage surfaces. Both temperatures and heat fluxes are needed to adequately specify the fire exposure.Direct comparisons between the average centerline temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The EDC-based combustion model and the common sub-grid scale turbulence model are satisfactory for the buoyancy-controlled, unconfined fire in crossflow. The CFD approach is much more realistic, when dealing with the characteristics of the wind-induced interaction of fires and large objects, than the simpler alternatives [13] ed by the buoyancy-induced air entrainment in the pool fire, preventing the flame from reaching fuselage. As illustrated in Figure 23, the extent of the higher heat flux to the wing skin rises with an increase of the wind speed to 10 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDC-based combustion model and the common sub-grid scale turbulence model are satisfactory for the buoyancy-controlled, unconfined fire in crossflow. The CFD approach is much more realistic, when dealing with the characteristics of the wind-induced interaction of fires and large objects, than the simpler alternatives [13] ed by the buoyancy-induced air entrainment in the pool fire, preventing the flame from reaching fuselage. As illustrated in Figure 23, the extent of the higher heat flux to the wing skin rises with an increase of the wind speed to 10 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst there has been research carried out over the years into the atmospheres associated with aircraft fires. Tests were conducted by Keltner [13] to simulate spilled fuel fires that might occur under the wing of a transport aircraft. The tests in general have been rather limited in terms of the fire-model used.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of large fires, which engulf objects, was experimentally and numerically studied by Gritzo and Nicolette. 7 The tests were conducted by Keltner et al 8 to simulate fuel spill fires that might occur under the wing of a transport aircraft. More recently, a considerable effort has been made by Suo-Anttila and Gritzo.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 in conducting a full-scale measurement of the temperature and heat flux distributions with the presence of a fuselage-sized cylindrical object engulfed in a large aviation-fuel fire subjected to various winds. All these works [7][8][9][10] showed that the flame zone geometry, the temperature, radiative property and velocity fields depend on a wide variety of parameters, including fuel type, wind condition and size of the object as compared to fire.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of large fires that engulf objects was experimentally and numerically studied by Gritzo [11]. Tests were conducted by Keltner [12] to simulate fuel spill fires that might occur under the wing of a transport aircraft. A considerable effort has been made by Suo-Anttila [5,6] in conducting a full-scale measurement of the temperature and heat flux distributions with the presence of a fuselage-sized cylindrical object engulfed in a large aviation fuel fire subjected to various winds.…”
Section: Introductionmentioning
confidence: 99%